1998
DOI: 10.1074/jbc.273.28.17689
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Chromosomal Localization, Tissue Distribution, and Functional Expression of the Human Pancreatic Sodium Bicarbonate Cotransporter

Abstract: We report the cloning, sequence analysis, tissue distribution, functional expression, and chromosomal localization of the human pancreatic sodium bicarbonate cotransport protein (pancreatic NBC (pNBC)). The transporter was identified by searching the human expressed sequence tag data base. An I.M.A.G.E. clone W39298 was identified, and a polymerase chain reaction probe was generated to screen a human pancreas cDNA library. pNBC encodes a 1079-residue polypeptide that differs at the N terminus from the recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
232
2
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(251 citation statements)
references
References 42 publications
12
232
2
4
Order By: Relevance
“…pNBC1 transcripts have also been detected in many organs, indicating the ubiquitous expression of this transporter (1). The second known NBC1 protein variant, kNBC1, is more restricted in its tissue expression and has thus far been detected in kidney and eye (8,29).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…pNBC1 transcripts have also been detected in many organs, indicating the ubiquitous expression of this transporter (1). The second known NBC1 protein variant, kNBC1, is more restricted in its tissue expression and has thus far been detected in kidney and eye (8,29).…”
Section: Discussionmentioning
confidence: 92%
“…kNBC1 mediates the majority of basolateral HCO 3 Ϫ efflux in the renal proximal tubule (2,9,26,29). pNBC1 is highly expressed in pancreas and various other tissues (1,8,14,20,21). An electroneutral NBC, NBC3 in humans (rat ortholog NBCn1) mediates Cl Ϫ -independent and stilbene-insensitive Na ϩ -HCO 3 Ϫ cotransport in various tissues (10,20,22,25).…”
mentioning
confidence: 99%
“…In pancreas, pNBC1 is thought to mediate HCO 3 Ϫ uptake into pancreatic duct cells in response to hormonal stimulation (3). However, expression of kNBC1 is almost completely limited to the kidney (9), where it mediates constitutive HCO 3 Ϫ exit from proximal tubules (3). However, the molecular mechanism underlying these different physiological roles of NBC1 variants has not been elucidated.…”
mentioning
confidence: 99%
“…Despite their high sequence similarity, these NBC1 variants are thought to have quite different physiological roles. pNBC1 is predominantly expressed in the pancreas, and lower levels are expressed in several organs, including the brain and eyes (9,13). In pancreas, pNBC1 is thought to mediate HCO 3 Ϫ uptake into pancreatic duct cells in response to hormonal stimulation (3).…”
mentioning
confidence: 99%
“…Others subsequently described inwardly directed electrogenic Na/HCO 3 cotransporters in several mammalian cells, including pancreatic duct cells [20,21]; we functionally identified it in rat astrocytes [22]. Kurtz [23], as well as our group [24], cloned the "pancreatic" NBCe ( Figure 2: NBCe1-B), which is a splice variant of NBCe1-A. We also cloned a "brain" NBCe ( Figure 2: NBCe1-C) [25], and showed that an NBCe protein is present in astrocytes [25] and the basolateral membrane of pancreatic duct [26].…”
Section: Electrogenicmentioning
confidence: 99%